Awareness and attitude regarding human papilloma virus, its vaccine and HPV vaccination acceptability among medical undergraduate students in Central India - Shegokar, Priyanka; Ukey, Ujwala; Narlawar, Uday; Barela, Shamvel (International Journal Of Community Medicine And Public Health, 2025)
Background: India is a major contributor to the global burden of human papilloma virus infection. Cervical cancer is the leading cause of death globally as well as in India. Highest prevalence observed among adolescents and young adults. Vaccination against HPV is an important mode of primary prevention against cervical cancer. As future healthcare providers, medical students can significantly influence community perspectives and HPV vaccine adoption; thus, cultivating the right mindset in them is essential to expedite its implementation for societal benefit. Methods: A cross-sectional study was conducted among 524 medical undergraduate students in government medical college. Data was collected using a pre-designed semi-structured self- administered questionnaire, entered into Microsoft Excel, and analysed. Results: The study of 524 medical undergraduates in central India found that while most participants (75.95%) were aged 19-24 and predominantly female (58.78%), awareness of HPV and its vaccine was moderate. Although cervical cancer and genital warts were commonly recognized as HPV-related, knowledge of other associated cancers was limited. Nearly 29% were unaware of any HPV vaccine. High vaccine cost (50%) and limited awareness (20%) were key barriers to uptake, highlighting the need for improved education and affordable access. Conclusions: This study found moderate but insufficient awareness of HPV and its vaccine among medical students in Central India. Many lacked knowledge of HPV-related cancers and vaccines like Gardasil-9, with cost and access as major vaccination barriers. Strengthening education is essential to improve vaccine uptake and reduce HPV-related disease burden.